2014
DOI: 10.1039/c4cc06205a
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of transcription factors using an Ag+-stabilized self-assembly triplex DNA molecular switch

Abstract: Based on a Ag(+)-stabilized self-assembly triplex DNA molecular switch (Ag(+)-STDMS), a simple, enzyme-free and sensitive new fluorescent strategy for detection of transcription factors was developed, achieving high sensitivity towards purified targets and real biological samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
1
23
0
2
Order By: Relevance
“…7, the florescence response increased proportionally to the concentration of target from 5 ng/μL to 50 ng/μL. The correlation equation wasΔF = 9.24C﹢2.41 (R = 0.998, C: ng/μL) and LOD calculated by the triple signal-to-noise method was 1.5 ng/μL, which was comparable to the previously reported method [41]. The result indicated that the assay was promising for practical application.…”
Section: Real Sample Analysissupporting
confidence: 79%
“…7, the florescence response increased proportionally to the concentration of target from 5 ng/μL to 50 ng/μL. The correlation equation wasΔF = 9.24C﹢2.41 (R = 0.998, C: ng/μL) and LOD calculated by the triple signal-to-noise method was 1.5 ng/μL, which was comparable to the previously reported method [41]. The result indicated that the assay was promising for practical application.…”
Section: Real Sample Analysissupporting
confidence: 79%
“…[41] Specific TFO probes can be used to detect target duplex DNAstrands through the formation of Hoogsteen or reverse Hoogsteen interactions,f orming parallel or antiparallel triplex structures. [45] Thef luorophore in the triplex assembly,stabilized by Ag + ions,isquenched by TFO 14.I nt he presence of the TF,a nd the competitive binding of TF with the duplex 12/13 releases the quenchermodified strand 14.T hus,a st he concentration of the transcription factor increases,t he resulting fluorescence generated by the sensing module intensifies ( Figure 5D). [43] Tr iplex formation triggers the opening of the hairpin, which leads to the fluorophore/quencherseparated triplex structure and thus results in an increase in the fluorescence of the system as the concentration of the duplex analyte is increased ( Figure 5B).…”
Section: Supramolecular Dna Triplex Switches For Sensingmentioning
confidence: 99%
“…[44] Furthermore, triplex-forming oligonucleotides were applied for the detection of non-DNAtargets.For example, Figure 5Coutlines the use of af unctional triplex structure composed of the fluorophore-modified duplex 12/13 and the quencher-functionalized TFO 14 as afunctional assembly for the sensing of the NF-kB p50 transcription factor (TF). [45] Thef luorophore in the triplex assembly,stabilized by Ag + ions,isquenched by TFO 14.I nt he presence of the TF,a nd the competitive binding of TF with the duplex 12/13 releases the quenchermodified strand 14.T hus,a st he concentration of the transcription factor increases,t he resulting fluorescence generated by the sensing module intensifies ( Figure 5D). The sensing system allowed the analysis of the transcription factor with as ensitivity corresponding to 40 pm.…”
Section: Triplex-forming Oligonucleotides For Dna and Aptamer Ligand mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, since the TFO binds to its dsDNA counterpart by means of the much weaker Hoogsteen/reverse‐Hoogsteen hydrogen bonding relative to the typical Waterson–Crick hydrogen bonding for dsDNA, the triplex is more flexible than dsDNA in nature and thus has found broad applications in molecular switches, nanodevices, and drug release . Furthermore, researchers have developed various promising sensors using the triplex structure as the fundamental element for DNA/protein analysis, detection of toxic metal ions/small biomolecules, and even cancer cell identification …”
Section: Introductionmentioning
confidence: 99%